Design of a Two-Phase PMSM Fed by an AC-AC Converter - Aydogmus, Omur; Deniz, Erkan (Ieee, 2015)
A two-phase permanent magnet synchronous motor is designed for using an AC-AC converter drive system fed from a single-phase source. This motor and drive system are proposed to replace with a traditional single-phase motors fed by electricity grid for improving the efficiency of the system. The proposed AC drive system can be connected directly between AC grid and motor without requiring any storage device such as DC-link large capacitors and rectification. The structure of AC-AC converter and modulation technique is presented with vector controlled two-phase PMSM. The converter output voltage and current waveforms and harmonic contents are analyzed with MATLAB simulation program. Additionally, responses of the motor speed and torque are presented for various conditions.
IEEE International Conference on Industrial Technology (ICIT) -- MAR 17-19, 2015 -- Seville, SPAIN
Keywords: AC-AC converter; AC motor drive; PMSM